Nothing ventured [large type] - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- William Warwick novels., 2019)
Much to his father's dismay, William Warwick rejects a career in law to join London's Metropolitan Police Force. He advances from a beat cop to a detective in Scotland Yard's arts and antiquities squad. Investigating the theft of a priceless Rembrandt painting, William meets and falls in love with Beth Rainsford, a gallery research assistant. As William searches for the missing masterpiece, he comes up against art collector Miles Faulkner and his brilliant lawyer, who are willing to bend the law to stay one step ahead of William. Meanwhile, Faulkner's wife, Christina, befriends William, but whose side is she really on?